NURSES’ AWARENESS, CONCERN, MOTIVATION, AND BEHAVIOR TOWARD HEALTH AND CLIMATE CHANGE - Manik, Marisa Junianti; Agustin, Angel; Immanuel, Chandra; Putri, Retno Pramita; Sihaloho, Shinta M.J.P. (Universitas Pelita Harapan, 2024)
Climate change significantly impacts health, food security, housing, safety, and work through long-term shifts in temperature and weather patterns. In Jakarta, these changes have led to the city experiencing the worst air pollution in Indonesia, with an Air Quality Index (AQI) score of 161. Nurses play a vital role in educating the public about behavioral changes to mitigate the effects of climate change. This study aimed to assess nurses' awareness, concerns, motivation, and behaviors related to health and climate change in a private hospital in Jakarta. This quantitative descriptive study involved 92 respondents selected through purposive sampling. The data were collected using the Climate, Health, and Nursing Tool (CHANT) questionnaire. The analysis revealed that nurses' awareness of evidence-based information on climate change ranged from